FOREX ROBOT DEVELOPMENT IN THE PERSPECTIVE OF LAW ENFORCEMENT INTELLIGENCE AND INTELLIGENCE STRATEGY - Seala Syah Alam; A Josias Simon Runturambi (International Journal of Social Science, 2021)
In the development of technology in the financial world, we are also now familiar with trading robots. This robot works to make it easier to trade in cyberspace. Trading robots do not offer a solution to generate instant profitable transactions. Profitable long-term forex trading is much more than just tactical analysis of forex trading and the use of trading robots. Have a special program that does all the work to look tempting. But this is how trading robot’s work. Trading robot sellers who prefer to see a decent trading robot. Such a system requires constant human adaptation and supervision. The general public who wants to use trading robots well must know the risks and systems of the trading robot and there is no guarantee that using a trading robot will be 100% profitable. It should be emphasized again that the trading robot will make decisions based on the conditions that have occurred and the right decisions at that time. Thus, no foreign trade organizer dares to give absolute guarantees.